Persona ética y organización: hacia un nuevo paradigma organizacional - Rodríguez, Alfredo (2005)
In many corporations, the importance of ethics does not go further than just good intentions. Philosopher Josef Pieper warned about this situation when he wrote about prudence, a virtue that is at the basis of outstanding management and thus, also of company ethics and corporate social responsibility, an issue included in the problem as there are many ways to understand its significance. However, before any consideration on the importance of company–social relationships or on the values and moral actions of organizations, we must bear in mind that the type of corporation depends on the type of individual we represent in our minds. Without an anthropological vision it is not possible to ascertain the actions of people in the corporation or their attitudes towards its goals. Our work will try to contribute a proposal in which the corporation is explained and organized from the point of view of the people.